Prevalence and risk factors associated with the occurrence of musculoskeletal pain in socioeducational agents - Patrícia Bittencourt Toscani Greco; Tânia Solange Bosi de Souza Magnago; Emanuelli Mancio Ferreira da Luz; Juliana Dal Ongaro; Bruna Pereira Chagas; Angela Isabel dos Santos Dullius (Rev Rene)
Objective: to verify the prevalence and associated factors of musculoskeletal pain in socio-educational agents. Methods: cross-sectional study with 381 socio-educational agents using a form addressing issues related to socio-demographic profile, work, habits and health, as well as musculoskeletal pain assessment. Data were analyzed using descriptive and analytical statistics, with a significance level of 5%. Results: socio-educational agents were predominantly female (55.8%) with mean age of 44.4 years (± 8.17). The mean pain intensity score was 5.03 (± 3.12); 43.0% participants reported low/moderate pain, and 39.9%, strong/unbearable pain. Conclusion: the prevalence of musculoskeletal pain was 82.9%. The associated factors were work leave of up to 24 days, psychological counseling and less than 8 daily sleeping hours.